A review of the threats to adult survival for swallows (Family: Hirundinidae). Issue 2 (3rd April 2019) - Imlay, Tara L.; Leonard, Marty L.
ABSTRACT: Capsule: For declining migratory birds, including many aerial insectivores, such as swallows, there is evidence that adult survival is a demographic process with strong effects on population trends. Aims: The aim was to identify and quantify the effect of threats affecting adult survival and potentially driving population declines for five well-studied swallow species: Barn Swallow Hirundo rustica, Cliff Swallow Petrochelidon pyrrhonota, Tree Swallow Tachycineta bicolor, Sand Martin Riparia riparia, and Purple Martin Progne subis . Methods: We reviewed the literature to identify the threats to adult survival, quantified the magnitude of the effect and identified whether threats had a direct or indirect effect on survival. Results: We identified habitat change, weather, competition, incidental loss, contaminants, insect availability, disease, and predation as threats to adult survival in swallows, although for many of these threats there was limited information to quantify their impact. However, weather, particularly cold snaps and precipitation, had negative effects on survival for many populations of four species, either directly or indirectly through effects on insect availability. When there was a relationship, weather was associated with a 13–53% decrease in survival. Conclusion: Based on the available research, weather conditions throughout the annual cycle is a key threat to adult survival for several swallow species. However, future research on the threats to these species should consider examining the effect of insect availability and the effect of threats during the non-breeding period on survival. Finally, we suggest that new research should be devoted to understanding the importance of adult survival for declining bird populations.